Can the public be trusted? : on the promise and perils of voluntary compliance / Yuval Feldman, Bar-Ilan University. - Feldman, Yuval, 1971- (Cambridge University Press, 2025)
When do citizens voluntarily comply with regulations rather than act out of fear of sanctions? Can the Public be Trusted? challenges prevailing regulatory paradigms by examining when democratic states can rely on voluntary compliance. Drawing on behavioral science, law, and public policy research, Yuval Feldman explores why voluntary compliance, despite often yielding superior and more sustainable outcomes, remains underutilized by policymakers. Through empirical analysis of policy implementation in COVID-19 response, tax compliance, and environmental regulation, Feldman examines trust-based governance's potential and limitations. The book presents a comprehensive framework for understanding how cultural diversity, technological change, and institutional trust shape voluntary cooperation. By offering evidence-based insights, Feldman provides practical recommendations for balancing trust, accountability, and enforcement in regulatory design. This book is essential reading for scholars, policymakers, and practitioners seeking to optimize regulatory outcomes through enhanced voluntary compliance. This title is also available as open access on Cambridge Core.